Interaction between Akkermansia muciniphila and Diet Is Associated with Proinflammatory Index in School-Aged Children - Juan Carlos Ayala-García; Alba Mariel García-Vera; Alfredo Lagunas-Martínez; Yaneth Citlalli Orbe-Orihuela; Ana Cristina Castañeda-Márquez; Cinthya Estefhany Díaz-Benítez; Víctor Hugo Bermúdez-Morales; Miguel Cruz; Margarita Bahena-Román; Ana Isabel Burguete-García (MDPI AG, 2023)
Background: Imbalance in the intestinal microbiota can lead to chronic low-grade inflammation. Diet may influence this association. In this study, we aimed to evaluate the interaction between Akkermansia muciniphila (A. muciniphila) and dietary patterns using a proinflammatory index. Methods: We conducted a cross-sectional study with school-aged children. We quantified the relative abundance (RA) of A. muciniphila in feces using a polymerase chain reaction. We collected dietary information through employing a food frequency questionnaire and generated dietary patterns using principal component analysis. We generated a proinflammatory index from serum levels of interleukin-6, interleukin-10, tumor necrosis factor alpha, and adiponectin validated by receptor operating characteristic curves. We evaluated the association between A. muciniphila and the proinflammatory index using logistic regression, including an interaction term with dietary patterns. Results: We found that children with a low RA of A. muciniphila and a high intake of simple carbohydrates and saturated fats had increased odds of being high on the proinflammatory index. However, when the consumption of this dietary pattern is low, children with a low RA of A. muciniphila had decreased odds of being high on the proinflammatory index. Conclusions: Our results suggest that the simultaneous presence of A. muciniphila and diet have a more significant impact on the presence of being high on the proinflammatory index compared to both factors separately.